PENGARUH DISIPLIN KERJA, MOTIVASI TERHADAP KINERJA PERAWAT DI RSUD (Rumah Sakit Umum Daerah) SIBUHUAN KAB. PADANG LAWAS - -, Nur Jamiah Reniati Hakim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research aims to determine the influence of work discipline and motivation on the performance of nurses at RSUD Sibuhuan District Hospital. Padang Lawas. The population in this study was 36 nurses, and the sample was 36 people using the census method or saturated sampling technique, namely taking the entire existing population. This research was carried out using primary data collected from respondents through questionnaires as an instrument to prove the research results. In order to analyze data, this research applied multiple linear regression analysis by using SPSS to see the influence of the independent variable on the dependent variable. From the results of the analysis, it was known that the value of the work discipline variable (X1) had a calculated f value greater than the f table, namely (3,586 > 2.035) with a significant value of 0.001 <0.05 which indicated work discipline variable (X1) has a partially significant effect on performance (Y). Then, the value of the motivation variable (X2) had a calculated f value greater than the f table (6,160 > 2.035) with a significance of 0.000 <0.05, which indicated the motivation variable (X2) has a partial effect on performance (Y). Furthermore, the results also showed that the calculated f had a value greater than the f table, namely (21.393 > 3.28), so it can be concluded that the variables monkey discipline (X1) and motivation (X2) have a significant effect simultaneously on performance (Y).